PENGARUH MICRO-INFLUENCER TERHADAP IMPULSIVE BUYING PRODUK SKINTIFIC DI TIKTOK SHOP MELALUI FEAR OF MISSING OUT (FOMO) PADA MAHASISWA GENERASI Z DI KOTA MAKASSAR - Amelia Christina Pairunan; Muhammad Ilham Wardhana Haeruddin; Nurul Fadilah Aswar; Chalid Imran Musa; Rahmat Riwayat Abadi (Bajang Institute, 2026)
This study examines the influence of micro-influencers on impulsive buying behavior of Skintific skincare products on TikTok Shop, with Fear of Missing Out (FOMO) as a mediating variable among Generation Z students in Makassar. The study is motivated by the increasing use of micro-influencers in digital marketing and the tendency of Generation Z to make impulsive purchases after exposure to social media content. This study employs a quantitative approach using a survey method through questionnaires. The population consists of Generation Z university students in Makassar who actively use TikTok and have purchased Skintific products through TikTok Shop. A total of 130 respondents were selected using random sampling techniques. Data were analyzed using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS) with SmartPLS 3.2.9. The results show that micro-influencers do not have a significant direct effect on impulsive buying. However, micro-influencers have a positive and significant effect on FOMO, which also has a positive and significant effect on impulsive buying. In addition, micro-influencers indirectly influence impulsive buying through FOMO. These findings indicate that feelings of missing out on trends or information triggered by micro-influencer content play an important role in driving impulsive buying behavior among Generation Z. This study highlights the importance of emotional factors, particularly FOMO, in enhancing the effectiveness of influencer-based digital marketing strategies.